PENINGKATAN MOTIVASI DAN KINERJA GURU PAI MELALUI VARIABEL SUPERVISI, KOMPENSASI DAN KOMPETENSI - Ikhrom, Ikhrom (Kopertais Wilayah X Jawa Tengah, 2014)
AbstractThis discussion aims to answer two problems, namely (1) is there any effect ofsupervision, compensation, and competency to work’s motivation? (2) is thereany effect of supervision, compensation, and competence on the teacherperformance either directly or indirectly ( through the work motivation)? Theresults of the path analysis testing phase I can concluded that supervision,compensation, competencies significantly effect to work’s motivation. Throughmultivariate regression analysis resulted in a significant influence. Competencyeffective contribution of 14.4 %, amounting to 1.5 % of compensation, andsupervision by 0.8 %. While the results of the partial regression test producessome conclusion, (1) the supervision effect but not significant with a score of0.029 and β scores sig 0.673 ( greater than 0.05 ), (2) the compensation effect is not significant with a score of 0.123 and β scores sig 0.075 (greater than 0.05), and ( 3 ) a significant effect of competence with a score of 0.380 and β sig score of 0.000 ( less than 0.05 ). The result of path analysis of phase II can be cocluded that supervision, compensation, competencies, and motivation together to significantly affect to the performance of Islamic religious teachers. While explaining the partial regression test, supervision and competence have asignificant effect, while compensation and motivation but not significant effect.Furthermore, after the model test found that supervisors supervise directly affect performance. Supervision has a direct effect score is greater than the indirect effect scores. Compensation does not affect the performance directly, but through motivation. Because scores directly effect compensation is smaller than the indirect effect. Competence directly effect performance significantly. Because the direct influence competence scores greater than the indirect effect scores.Effective contribution of each variable is different. Supervision effectivecontribution by 4.81 %. Compensation effective contribution of 0.1 %.Competency effective contribution by 64 %, and the contribution of effectivemotivation of 0.7 %. Based on the results of the study found, the elementaryteacher PAI’s performance can be improved through the supervision,compensation through motivation, competence, and other variables that are notincluded in the study.Keyword: motivasi, kinerja guru PAI, supervisi, kompensasi, kompetensi